2018
DOI: 10.22158/jecs.v2n3p191
|View full text |Cite
|
Sign up to set email alerts
|

The Micro-Politics of Schooling in Lesotho: Bullying

Abstract: The paper is based on a study undertaken in 2015

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…For example, some studies carried out in Africa show that bullying and other forms of violence are real issues of concern in schools. Liang (2007) found that; out that of 5074 Grade 8 and 11 students surveyed in the educational system in South Africa, 19.3 percent were victims of bullying, while Makafane and Khalanyane (2018) found out that there are several forms of bullying in Lesotho schools some of which are physical, verbal and cyber related. This is testimony that bullying is a worldwide problem in schools; and thus regarded as a form of low level violence that can escalate and become physical and even lethal (Olafsen & Viemero, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For example, some studies carried out in Africa show that bullying and other forms of violence are real issues of concern in schools. Liang (2007) found that; out that of 5074 Grade 8 and 11 students surveyed in the educational system in South Africa, 19.3 percent were victims of bullying, while Makafane and Khalanyane (2018) found out that there are several forms of bullying in Lesotho schools some of which are physical, verbal and cyber related. This is testimony that bullying is a worldwide problem in schools; and thus regarded as a form of low level violence that can escalate and become physical and even lethal (Olafsen & Viemero, 2012).…”
Section: Introductionmentioning
confidence: 99%